Predicting police behavior: Ecology, class, and autonomy - Miller, J. Mitchell (American journal of criminal justice, 1994)
Social ecological theories of crime have recently been extended to explain spatial variation in police behavior. Although these theories successfully identify community characteristics affecting local policing, they fail to acknowledge the class-based origins of formal social control and the relative autonomy of the police. This paper addresses the neglected class issue by integrating social ecological and critical theories in a model of police behavior. Cross-sectional data was obtained from twenty-five police agencies’ vice divisions and their corresponding jurisdictions to test the integrated hypothesis. Four social ecological variables and a fiscal measure of relative autonomy are examined as police behavior predictors. Findings reveal that both the autonomy measure and three of the social ecological variables explain significant variance in police behavior, thus supporting the inclusion of structural Marxism in a general theory of police behavior.